QUYOSH BATAREYALARI YORDAMIDA OLINADIGAN ENERGIYA MIQDORINI SIRTNING YORITILGANLIGIGA BOG‘LIQLIGI - Aliqulov, Muysin (Innovatsion texnologiyalar, 2022)
The dependence of the amount of energy obtained with the help of solar cells on the illumination of the surface of the solar cell have been studied in this work. It was shown using the created device that the smaller the angle between the normal and the incident sunlight, transferred to the surface of the solar cell, the higher the illumination.